"O rio Tocantins dá vida aos pescadores, a UHE - Estreito tira": uma análise antropológica das mudanças socioambientais percebidas pelos pescadores da colônia Z7 no rio na altura de Tocaninópolis - TO - Silva, Josiane de Jesus Martins (Universidade Federal do Tocantins, 2023)
This research aimed to reflect on the universe of Colonia de Pescadores Z7 in the municipality of Tocantinópolis-TO. Starting from an ethnographic description of this fishing cultural universe to arrive at its most current dilemmas. Followed by a brief historical overview of the community, demonstrating its importance for Tocantins society and ending with a reflection that is the central point of this discussion that seeks to elucidate the reader, the impacts that this community and the surrounding cities suffered with the construction of another energy project on the Tocantins River, above this community.